Heat transfer performance of magnetohydrodynamic multiphase nanofluid flow of Cu–Al2O3/H2O over a stretching cylinder - Alshehry Azzh Saad; Yasmin Humaira; Ganie Abdul Hamid; Shah Rasool (Open Physics, 2023)
This study examines the heat transfer properties of a recently created hybrid nanofluid in contrast to a traditional nanofluid. The aim is to improve the transfer of heat in the flow of the boundary layer by employing this novel hybrid nanofluid. Our study investigates the impact of the Lorentz force on a three-dimensional stretched surface. We utilize a new model that incorporates thermo-physical factors. A quantitative parametric study is performed to investigate the influence of different physical parameters, enabling meaningful comparisons. The results demonstrate that the hybrid nanofluid exhibits a higher heat transfer rate compared to the conventional fluid, even in the presence of a magnetic field. Moreover, the efficiency of heat transfer can be enhanced by modifying the concentration of nanoparticles in the hybrid nanofluid.